RÉGÉNÉRATION IN VITRO DE L’ARBRE À SUIF (PENTADESMA BUTYRACEA SABINE), UNE ESPÈCE LIGNEUSE À USAGES MULTIPLES (LUM) VULNÉRABLE AU BENIN - S.S., Houédjissin; S.J., Dangou; P., Azokpota; G., Cacaï; A., Agbidinoukoun; D. J., Hounhouigan; C., Ahanhanzo (European Scientific Journal, ESJ, 2015)
This work is done in order to identify the effects of basal media associated with two cytokinins (BAP and zeatin) and suitability for the regeneration of apical and axillary buds Pentadesma butyracea. Fragments axillary bud stem and apical bud stem fragment were taken from seedlings P. butyracea from seed germination in a greenhouse. After disinfection, explants were cultured on three basic areas: MS (Murashige and Skoog), B5 (Ganborg) and WPM (Woody Plant Medium). The effects of Zeatin and BAP on the bud and bud development were also studied. These in vitro propagation of tests conducted in this species, showed that the apical bud fragments proved to be the most favorable. Among the tested culture media, basal medium Gamborg (B5) is most suited to the entry into operation of apical buds (26.66%). Other WPM and MS basal media also allowed bud but at low rates (20%; 13%). Zeatin (3.5 mg / L) appears best suited to budding and regeneration of apical buds of P. butyracea and the formation of leaves per explants. BAP favored the resumption of activity of the apex, but not plant development. Our experiments allow to open a new path consistent multiplication of individuals elites Pentadesma butyracae to produce seeds that can be used for propagation, domestication and conservation of this species.